2023
DOI: 10.1055/a-1977-8848
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-32 Suppression: its Effects on Prostate Cancer Cells’ Capability to Proliferate and Migrate

Abstract: Introduction This paper sought to scrutinize the role of microRNA-32 (miR-32) on the growth and migration as well as on the expression of metastatic genes in PC3 cells of prostate cancer in vitro. Methods Subsequent transfection of cells with miR-32 mimics, miR-32 inhibitor, negative control (NC), cell proliferation using MTT, and apoptosis by ELISA were performed. Furthermore, qRT-PCR was directed to measure the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Animal models of various cancers and clinical studies showed that there is a causal relationship between miRNAs and cancer development, and as a result, miRNAs quickly entered the clinical stage as biomarkers and therapeutic targets. [42][43][44][45] miRNAs can act as promoters or tumor suppressors to induce resistance to chemo/radiotherapy in cancer through DNA damage repair and the inhibition of apoptosis. 46 The target of miRNAs can be a tumor suppressor gene.…”
Section: Mirnas In Cancer Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Animal models of various cancers and clinical studies showed that there is a causal relationship between miRNAs and cancer development, and as a result, miRNAs quickly entered the clinical stage as biomarkers and therapeutic targets. [42][43][44][45] miRNAs can act as promoters or tumor suppressors to induce resistance to chemo/radiotherapy in cancer through DNA damage repair and the inhibition of apoptosis. 46 The target of miRNAs can be a tumor suppressor gene.…”
Section: Mirnas In Cancer Therapymentioning
confidence: 99%
“…An aberrant expression of one miRNA can affect hundreds of mRNAs and has a profound effect on cancer‐related signaling pathways. Animal models of various cancers and clinical studies showed that there is a causal relationship between miRNAs and cancer development, and as a result, miRNAs quickly entered the clinical stage as biomarkers and therapeutic targets 42–45 . miRNAs can act as promoters or tumor suppressors to induce resistance to chemo/radiotherapy in cancer through DNA damage repair and the inhibition of apoptosis 46 .…”
Section: Mirnas In Cancer Therapymentioning
confidence: 99%